Colesteatoma: tomografia computadorizada e radiografia em cão com otite crônica - Belotta, Alexandra Frey [UNESP]; Babicsak, Viviam Rocco [UNESP]; Arruda, Vanessa Kurtz de [UNESP]; Amorim, Rogério Martins [UNESP]; Mamprim, Maria Jaqueline [UNESP]; Vulcano, Luís Carlos [UNESP] (My University, 2012)
Cholesteatoma, a rare and/or misdiagnosed disease, results of a serious complication in dogs with chronic otitis. This article describes a case of a dachshund sent to the veterinary hospital presenting signs of cognitive dysfunction associated to peripheral neuropathy of the facial nerve on the right side. At radiography, an enlargement and thickness of the contours associated with loss of anatomical definition of the right tympanic bulla compared to the left was seen. At tomography, this enlargement and thickness were seen with better definition, besides the fulfilling by hiperdense calcified content, bullae osteolysis and temporal bone sclerosis at the same side.
Cholesteatoma: computed tomography and radiography in a dog
Keywords: Cholesteatoma; Dog; Radiography; Computed tomography